Proof in mathematics education: A bibliometric analysis using R biblioshiny and VOSviewer - Ridwan Ridwan; Haeruddin Haeruddin (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2026)
The modern mathematics curriculum internationally places proof as a central component that should be integrated from primary school to university. Empirical research on proof in mathematics education has grown rapidly in the last two decades; however, few studies have attempted to map this research landscape. This article provides a comprehensive mapping of research on proof through a bibliometric approach using the Web of Science Core Collection (WoSCC) database. Data from 157 articles published between 2016 and 2025 were analyzed using the biblioshiny R-package and VOSviewer. Results show that publication numbers fluctuated, peaking in 2024, with Dawkins et al. being the most cited and ZDM-Mathematics Education the most prolific source. Keyword analysis reveals six distinct clusters, with the USA as the leading contributor. Beyond these trends, the study identifies a significant shift toward the integration of artificial intelligence within the transition-to-proof process. These findings offer a strategic roadmap for researchers to bridge the gap between technological mediation and formal mathematical validation, emphasizing the need for instructional designs that harmonize generative tools with the rigorous construction of deductive proofs. Ultimately, this mapping highlights the urgency of ensuring that digital advancements support the authenticity of proving activities rather than merely facilitating the mechanical production of logical steps.